Republicanism in theory and practice - Honohan, Iseult, 1951-; Jennings, Jeremy, 1952- (Routledge, 2006)
Recent claims that civic republicanism can better address contemporary political problems than either liberalism or communitarianism are generating an intense debate. This is a sharp insight into this debate, confronting normative theory with historical and comparative analysis. It examines whether republican theory can address contemporary political problems in ways that are both valuable and significantly different in practice from liberalism. These expert authors offer contrasting perspectives on issues raised by the contemporary revival of republicanism and adopt a variety of.
Keywords: Republicanism.; Républicanisme.; POLITICAL SCIENCE -- Political Ideologies -- Democracy.; Republicanism